2021
DOI: 10.3892/ol.2021.12998
|View full text |Cite
|
Sign up to set email alerts
|

TAGLN2 promotes the proliferation, invasion, migration and epithelial‑mesenchymal transition of colorectal cancer cells by activating STAT3 signaling through ANXA2

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-associated mortality worldwide and currently ranks third in the USA in terms of prevalence. Transgelin-2 (TAGLN2) was previously reported to serve as a tumor promoter in various types of cancer. The present study aimed to investigate the role of TAGLN2 in the progression of CRC and to determine the potential underlying mechanism. The expression level of TAGLN2 in CRC cells (HCT116, SNU-C1, LoVo and SW480) were first detected by reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…To determine whether any of the most highly methylated genes discovered have been implicated in CRC, we performed in silico validation using published reports. Among the genes containing the top CpG sites shown in Table 1 are the genes ADAMTS2 , ADAMTS5 , ADARB2 , ADCY1 , ADHFE1 , AGRN , AKR1B1 , ANK1 , ANKRD13B , ANXA2 , AQP5 , ATP11A , BCAT1 , BEND5 , BOLL , CADM2 and CASR , which have been implicated in CRC [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. A complete list of all CpG sites significantly associated with CRC and the genes they map to, including DMRS in which they are located, is presented in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether any of the most highly methylated genes discovered have been implicated in CRC, we performed in silico validation using published reports. Among the genes containing the top CpG sites shown in Table 1 are the genes ADAMTS2 , ADAMTS5 , ADARB2 , ADCY1 , ADHFE1 , AGRN , AKR1B1 , ANK1 , ANKRD13B , ANXA2 , AQP5 , ATP11A , BCAT1 , BEND5 , BOLL , CADM2 and CASR , which have been implicated in CRC [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. A complete list of all CpG sites significantly associated with CRC and the genes they map to, including DMRS in which they are located, is presented in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The clinical significance of our investigation is that DNA methylation-based molecular markers have the promise for detection and clinical management of CRC. Although the DNA methylation biomarkers we discovered were not clinically validated, which could preclude their implementation in clinical practice, in silico validation revealed important aberrantly methylated genes including NPBWR1 , CDH12 , NR5A2 , DCLK1 , NKX2-2 , KIAA1026 , ADARB2 , MAGI2 , SMAD3 , GUCY1B3 , DOK6 , EFS and PCSK2 implicated in CRC [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], suggesting that if further confirmed these genes could serve as prognostic markers. For example, the cadherin-12 ( CDH12 ) gene has been shown to increase cancer cell migration, invasion and progression via promoting EMT by targeting the transcriptional factor Snail [ 52 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each of the markers we identified have previously been linked to human cancer, and thus are not limited in relevance to the murine model employed. Of these, Tagln2 has previously been linked to angiogenesis, proliferation, migration, and epithelial–mesenchymal transition in GC [ 25 , 26 ], while Mbl2 gene variants have been linked to risk of stomach cancer [ 27 ] and increased serum levels linked to pancreatic cancer [ 28 ]. In addition, Itih3 has previously been identified as a predictor of GC in mice and patients [ 29 ], while F12 is a prognostic marker for thyroid cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to UV rays causes the senescence-associated secretory phenotype (SASP) [ 20 ]. TAGLN is an actin-related protein, which is related to cell proliferation, migration, and invasion [ 21 , 22 ]. Studies on TAGLN found that its imbalance can promote the development of rectal, breast, and colorectal cancers, and is considered to be a tumor suppressor [ 23 26 ].…”
Section: Discussionmentioning
confidence: 99%